2017
DOI: 10.17795/zjrms-5920
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Silver Nanoparticles Synthesized by Using Extracts of Hedera helix

Abstract: Background: Silver nanoparticles (AgNPs) are one of the most widely applicable particles whose application is increasing in Nano world daily. Silver nanoparticles have expressed significant advances owing to wide range of applications in the field of bio-medical, sensors, antimicrobials, catalysts, electronics, optical fibers, agricultural, bio-labeling and the other areas. Green synthesis is the safe and easiest method of producing silver nanoparticles. Because of the production of the silver ions, silver nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Silver nanoparticles synthesised with the use of ivy extracts showed markedly higher antimicrobial activity against Gram-positive B. subtilis ATCC 1715 and Gramnegative K. pneumoniae ATCC 1290 strains in comparison to both AgNO 3 and raw plant extracts. Both these strains were characterised by similar sensitivity to silver nanoparticles and a similar growth inhibition zone under the influence of silver nitrate [Abbasifar et al 2017].…”
Section: Antibacterial Activitymentioning
confidence: 98%
“…Silver nanoparticles synthesised with the use of ivy extracts showed markedly higher antimicrobial activity against Gram-positive B. subtilis ATCC 1715 and Gramnegative K. pneumoniae ATCC 1290 strains in comparison to both AgNO 3 and raw plant extracts. Both these strains were characterised by similar sensitivity to silver nanoparticles and a similar growth inhibition zone under the influence of silver nitrate [Abbasifar et al 2017].…”
Section: Antibacterial Activitymentioning
confidence: 98%
“…They concluded that the nanoparticles had significantly higher antimicrobial activity than either the extract alone or AgNO 3 . 110 Saponin-rich ethanolic CI extracts were also used to improve bacterial metabolism in biodegradation processes. Zdarta et al 111 found that the extract enhanced the viability of the cells (Acinetobacter calcoaceticus) during the biodegradation process.…”
Section: ■ Physicochemical Properties Of CI Biomassmentioning
confidence: 99%
“…Their research focused on the antibacterial activity of the nanoparticles against two bacteria strains. They concluded that the nanoparticles had significantly higher antimicrobial activity than either the extract alone or AgNO 3 . Saponin-rich ethanolic CI extracts were also used to improve bacterial metabolism in biodegradation processes.…”
Section: Common Ivy Extractives and Their Applicationsmentioning
confidence: 99%
“…Research on Escherichia coli has confirmed that the accumulation of AgNPs on the cell membrane creates gaps in the bilayer's integrity, thereby increasing its permeability and resulting in bacterial cell death. Various studies have highlighted the strong correlation between the activity of AgNPs and their size ( Abbasifar et al, 2017 ; Ahmadi, 2020 ; Cai et al, 2012 ; Du et al, 2020 ; Elshazly et al, 2022 ; Hassan et al, 2016 ; Panda et al, 2011 ; Salem and Samir, 2018 ; Zachar, 2020 ). Infected wounds pose a significant challenge in healthcare, necessitating innovative therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%